Crystal structure and Hirshfeld surface analysis of 2-[(1,3-benzoxazol-2-yl)sulfanyl]-N-(2-methoxyphenyl)acetamide - Aydin, Abdullah; Celikesir, Sevim Turktekin; Akkurt, Mehmet; Saylam, Merve; Pabuccuoglu, Varol (International Union of Crystallography (IUCr), 2019)
In the title compound, C16H14N2O3S, the 1,3-benzoxazole ring system is essentially planar (r.m.s deviation = 0.004 Å) and makes a dihedral angle of 66.16 (17)° with the benzene ring of the methoxyphenyl group. Two intramolecular N—H...O and N—H...N hydrogen bonds occur, forming S(5) and S(7) ring motifs, respectively. In the crystal, pairs of C—H...O hydrogen bonds link the molecules into inversion dimers with R 2 2(14) ring motifs, stacked along the b-axis direction. The inversion dimers are linked by C—H...π and π–π-stacking interactions [centroid-to-centroid distances = 3.631 (2) and 3.631 (2) Å], forming a three-dimensional network. Two-dimensional fingerprint plots associated with the Hirshfeld surface show that the largest contributions to the crystal packing come from H...H (39.3%), C...H/H...C (18.0%), O...H/H...O (15.6) and S...H/H...S (10.2%) interactions.
Keywords: crystal structure; dimers; Crystallography; QD901-999; Hirshfeld surface analysis; hydrogen bonding; ,3-benzoxazole ring system; Research Communications; 3. Good health